2003
DOI: 10.1097/01.pcc.0000077079.42302.81
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome in children: Experience in a regional hospital in Hong Kong*

Abstract: Severe acute respiratory syndrome affects children, but the course is less severe. Nevertheless, the disease could have a significant psychosocial impact on children because of the potential seriousness of the disease in their adult family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
142
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(153 citation statements)
references
References 5 publications
(9 reference statements)
4
142
0
7
Order By: Relevance
“…[2][3][4] Although the validity of the multivariate analysis is limited by the small number of children in our cohort, it seems that sore throat, high neutrophil count at presentation, and peak neutrophilia are independent prognostic indicators for severe illness in terms of requirements for oxygen and intensive care. Furthermore, children Ͼ12 years of age are more likely to require methylprednisolone treatment because of severe illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Although the validity of the multivariate analysis is limited by the small number of children in our cohort, it seems that sore throat, high neutrophil count at presentation, and peak neutrophilia are independent prognostic indicators for severe illness in terms of requirements for oxygen and intensive care. Furthermore, children Ͼ12 years of age are more likely to require methylprednisolone treatment because of severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,[13][14][15] In pediatric series, including the present cohort, cough is a presenting feature for 43% to 91% of children and shortness of breath for 9% to 40%. [2][3][4] The WHO case definitions would have excluded 34% of the children with laboratory-confirmed SARS in the present cohort, which is the largest single-center, pediatric case series reported to date. The lack of sensitivity of the WHO case definitions for both adult and pediatric patients is disturbing, with respect to the effects on case management at the point of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most existing reports have focused on adult SARS patients, recent reports revealed that the clinical course was less severe in pediatric SARS patients than in adult SARS patients (8,9 ). On the whole, the outcomes of pediatric SARS patients have been favorable.…”
mentioning
confidence: 96%
“…Recent studies have reported that the clinical course is less severe in pediatric SARS patients than in adult SARS patients (8,9 ). A logical question would be whether the plasma SARS-CoV viral load in pediatric SARS patients is different from that in adult SARS patients.…”
mentioning
confidence: 99%